The Economic Factors Affecting to Lao Stock Exchange Index - SIPHANTHONG, Dr. Bounthavy; Duangdara, Chanthanome (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research on economic factors affecting the Lao Stock Exchange Index aims to: 1) identify economic factors affecting the Lao Stock Exchange Index in the long term and 2) identify economic factors affecting the Lao Stock Exchange Index in the short term. By using the collected data, analyzing it with inferential statistics to find the parameters of the regression equation through the long-term relationship model (Co-integration) using the Johansen and Juselius method, and analyzing the short-term equilibrium relationship (Error Correction Model: ECM) of the economic factors affecting the Lao Stock Exchange Index using the E-views 10 program. The results of the research found that: the correlation coefficient in the form of a correlation matrix of the independent variable with the independent variable has a correlation coefficient value of 45%, which shows that the correlation coefficient does not exceed 80%, indicating that there is no serious multi collinearity problem in the model. Therefore, through the examination of the properties of the model, it was also found that the decision coefficient R-squared = 0.5251, which means that the independent variables, namely the exchange rate fluctuation and the change in the consumer price index, can explain the long-term change in the Lao Stock Exchange Index by up to 52.51%. Therefore, the model for analyzing economic factors affecting the Lao Stock Exchange Index is applicable and depends on at least 1 factor. In addition, by using this data to test the effect of the independent variable on the dependent variable in the short run (adjustment from the short-run equilibrium to the long-run equilibrium), ECM (-1) found that the model for analyzing economic factors that affect the Lao Stock Exchange index in the short run is applicable and depends on at least one of the identified factors.